Pengaruh Promo Gratis Ongkir dan Live streaming terhadap Perilaku Impulsive Buying pada Mahasiswa Pengguna E-commerce (Shopee & TikTok Shop) di Kota Medan - Agnes Fransiska (Yayasan Literasi Emas Nusantara, 2026)
The swift expansion of e-commerce has altered buying habits of consumers, especially among college students. Promotions like free shipping and live streaming have emerged as successful marketing tactics employed by e-commerce sites to stimulate buying. These techniques can lead to impulsive spending habits, causing consumers to make spontaneous buys driven by emotional reactions and appealing deals. This research seeks to examine the impact of free shipping offers and live streaming on spontaneous purchasing behavior among college students utilizing Shopee and TikTok Shop in Medan City. This research utilized a quantitative correlational method. Data were gathered using an online survey circulated through Google Forms among university students in Medan who regularly utilize Shopee and TikTok Shop. The method employed for sampling was non purposive sampling. The gathered data were examined through multiple linear regression to assess the impact of free shipping promotions and live streaming on impulsive purchasing behavior. The results show that free shipping offers positively and significantly influence impulsive purchasing behavior. Live streaming demonstrates a notable and substantial effect on impulsive purchases. Both variables simultaneously have a significant impact on students' impulsive buying behavior. The regression model indicates that promotions for free shipping and live streaming significantly account for differences in impulsive buying behavior. The findings indicate that marketing approaches highlighting cost efficiency and engaging shopping experiences can successfully encourage impulsive buying. Promotions offering free shipping decrease perceived buying expenses, while live streaming boosts consumer interaction and confidence via live product displays. Consequently, e-commerce platforms can enhance these features to boost consumer buying intentions and sales performance.